THEORETICAL AND PRACTICAL ASPECTS OF FORMING, SUPPORTING AND INCREASING THE MOTIVATION OF MOBILIZED PERSONS FOR MILITARY SERVICE - Goman, Yurii; Bespalko, Andrii; Tsariuk, Serhii (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2025)
B a c k g r o u n d . The article examines approaches to understanding and the psychological essence of motivation; the components of the motivational sphere of the individual, motivation in the process of communication between the commander and the subordinate and how motivation affects the development of the individual are considered; methods of optimal motivation of a mobilized citizen for military service in the conditions of the legal regime of martial law are discussed and proposed. The results of the conducted theoretical and applied research provide grounds for asserting that the modern training system of the training centers of the Armed Forces of Ukraine faces the task of educating an initiative, socially active and motivated defender. After all, it is known that the high success of professional tasks is based not only on professionalism, but also on a developed system of self-motivation, awareness of one’s own motives and their identification in each serviceman. The formation of motivation for military service begins with the realization that service is the basis for ensuring the peace and security of our country. The motivation for service has deep roots: love for the Motherland, respect for military honor, the desire to be part of a team (a family of military personnel) working for our future Victory. It is supported by constant professional growth, the availability of thorough professional knowledge, mutual respect and self-confidence. M e t h o d s . Theoretical: analysis, generalization, comparison, systematization of scientific sources on the research problem. R e s u l t s . According to the results of the conducted research, the main components of the motivational sphere of the individual are determined, recommendations are developed for the formation, support and increase of motivation of persons called up for mobilization under the legal regime of martial law and undergoing basic military training. C o n c l u s i o n s . Motivation of people mobilized for military service is a complex process complicated by many factors. Especially if it occurs during a full-scale invasion, during an active information campaign by the enemy, which discredits the Ukrainian government and its society. Only a comprehensive approach to working with mobilized military personnel, taking into account their needs and characteristics can become a catalyst for positive changes for all stakeholders, help destroy negative stereotypes established in society and create positive prerequisites for defeating our archenemy.